Sistem Layanan Administrasi Pengelolaan Kerja Praktek Mahasiswa secara Online - Satria, Rahmat; Maita, Idria; Roni, Muhammad Fadil (Journal of Research and Investigation in Education, 2023)
Utilizing the role of technology in assisting in carrying out business processes that are being managed by an institution or institution is the right decision in today's digital era. This thinking of course also applies to the Information Systems Study Program (SI) of the State Islamic University (UIN) Sultan Syarif Kasim (Suska) Riau. As the number of students increases, it greatly affects the way in which academic services are provided in this study program. One of the academic services currently available is the process of taking and implementing the Job Training (KP) course. The stages of the process that must be carried out by students and the KP coordinator are referring to the Standard Operating Procedures (SOP) currently available in the study program. The stages of the KP process are 1 submitting a proposal, 2 completing all required documents, 3 waiting for the proposal selection, 4 receiving the announcement of the selection results and 5 appointing supervisors. All processes are currently carried out directly dealing with the Ko.KP in the study program. Of course this causes problems, one of which is the long processing time and documents are the main reason for requiring archive storage space which is less efficient at this time. The purpose of this research is to identify the feasibility of the proposed KP system, design the SI KP as a reference in building the system and apply the IS in the study program so that the KP process can run more effectively. The processed data comes from questionnaires distributed to students and the KP coordinator. Data processing techniques that have been collected using User Centered Design (UCD). The results of the evaluation of the SI Mock-up prototype with the agreed value of the KP system is 76.54%. The conclusion of this research can be continued, so that this researcher can produce SI KP which is implemented in the SI Study Program of UIN Suska Riau.